Investigating Students’ Awareness, Usage, and Perceptions of ChatGPT in Libyan Higher Education: A Case Study at the University of Benghazi in 2024 - Hamed, Aisha; Nadia Senussi (AlQalam Journal of Medical and Applied Sciences, 2025)
The world is experiencing rapid technological advancements, with efforts to integrate technology across all sectors. Artificial Intelligence (AI) is reshaping various industries, including education, making teaching and learning more efficient and accessible. One such tool, ChatGPT, has potential applications in education, but students need to understand both its benefits and risks. While ChatGPT can enhance learning when used properly, overreliance on it may hinder the learning process. This research examined students’ awareness of ChatGPT and their perceptions of its benefits and risks in academic and personal contexts. The study gathered quantitative data through surveys from 108 students across different disciplines at the University of Benghazi Qaminis branch, Libya. The findings reveal that while many students are familiar with ChatGPT, they do not consistently use it for educational purposes. Furthermore, several students recognize both the positive and negative impacts of ChatGPT on learning but believe that universities should provide more information on effectively incorporating it into learning activities. This study highlighted that while ChatGPT can support educational activities, proper guidance and training for students and lecturers are necessary to ensure its responsible and legal use, ultimately enhancing the educational process.